One hole spectral densities in the polarized t-j model - Hallberg, K.; Rojo, A. G.; Balseiro, C. A. (Comisión Nacional de Energía Atómica; Argentina)
Fil: Hallberg, K. Comisión Nacional de Energía Atómica; Argentina